2021
DOI: 10.3390/insects12100850
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and Ultrastructure of Galls Induced by Neuroterus quercusbaccarum (Hymenoptera: Cynipidae) on Oak Leaves (Quercus robur)

Abstract: The structure and ultrastructure of two developmental stages of the spangle gall induced by Neuroterus quercusbaccarum (Hymenoptera, Cynipidae) were investigated using light microscopy (LM), fluorescence microscopy (FM), and transmission (TEM) and scanning (SEM) electron microscopy. The general design of the gall structure was typical of Cynipidae, but some structural features distinguished the spangle gall. Previously undescribed, characteristic multicellular epidermal protuberances with large openings were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The CT imaging also revealed the small size of the attachment, approximately 0.2 mm, and showed the previously described calcium oxalate layer surrounding the larval growth chamber (Jankiewicz et al, 2021). The CT imaging shows the density differences of the internal structures of the gall and enables a 3D image of the entire gall structure to be built.…”
Section: Comparative Imaging Of the Sexual Generationsmentioning
confidence: 59%
See 2 more Smart Citations
“…The CT imaging also revealed the small size of the attachment, approximately 0.2 mm, and showed the previously described calcium oxalate layer surrounding the larval growth chamber (Jankiewicz et al, 2021). The CT imaging shows the density differences of the internal structures of the gall and enables a 3D image of the entire gall structure to be built.…”
Section: Comparative Imaging Of the Sexual Generationsmentioning
confidence: 59%
“…The CT imaging shows the density differences of the internal structures of the gall and enables a 3D image of the entire gall structure to be built. This approach provides a different prospective to the scanning electron images of these two galls currently published (Jankiewicz et al, 2017, Jankiewicz et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the central role cell walls play in determining the structure and function of plant tissues, little is known about how plant cell walls are modified during the development of insect galls. Previous qualitative studies have shown changes in lignin (Tanaka et al, 2013), tannins (Jankiewicz et al, 2021), and several polysaccharides (Formiga et al, 2013;…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, these dramatic modifications of host plants caused by gall inducers are usually accompanied by extensive reprogramming of plant gene expression [ 24 ]. Specifically, the expression modification of these genes affects the plant’s defense responses [ 25 , 26 ], hormone pathways [ 27 , 28 ], cell cycle, cell wall and cytoskeleton organization [ 29 , 30 ], developmental processes [ 31 , 32 ] and metabolic reprogramming [ 19 , 33 ]. Transcriptomic and metabolomic approaches can provide deep insights into the complexity of gall inducer–host plant interactions and offer reliable, multidimensional molecular biology information for studying and controlling gall inducers [ 17 , 27 , 34 ].…”
Section: Introductionmentioning
confidence: 99%